Anti-HER2 biparatopic antibody KJ015 has near-native structure, functional balanced high affinity, and synergistic efficacy with anti-PD-1 treatment in vivo - Zheng Wang; Yu Liu; Yunxia Xu; Lin Lu; Zhen Zhu; Baojie Lv; Xin Fang; Yao Tang; Jinhua Wang; Yu Cheng; Ying Hu; Junwen Lou; et al. (mAbs)
Currently approved human epidermal growth factor receptor 2 (HER2)-targeted antibody therapies are largely derived from trastuzumab, including trastuzumab-chemotherapy combinations, fixed-dose trastuzumab-pertuzumab combinations, and trastuzumab antibody-drug conjugates. To expand the options, bispecific antibodies, which may better utilize the benefits of combination therapy, are being developed. Among them, biparatopic antibodies (bpAbs) have shown improved efficacy compared to monoclonal antibody (mAb) combinations in HER2-positive patients. BpAbs bind two independent epitopes on the same antigen, which allows fine-tuning of mechanisms of action, including enhancement of on-target specificity and induction of strong antigen clustering due to the unique binding mode. To fully utilize the potential of bpAbs for anti-HER2 drug development, it is crucial to consider formats that offer stability and high-yield production, along with a functional balance between the two epitopes. In this study, we rationally designed a bpAb, KJ015, that shares a common light chain with two Fab arms and exhibits functionally balanced high affinity for two HER2 non-overlapping epitopes. KJ015 demonstrated high-expression titers over 7 g/L and stable physicochemical properties at elevated concentrations, facilitating subcutaneous administration with hyaluronidase. Moreover, KJ015 maintained comparable antibody-dependent cytotoxicity, phagocytosis, and complement-dependent cytotoxicity with trastuzumab plus pertuzumab. It exhibited enhanced synergy when administered subcutaneously with hyaluronidase and anti-PD-1 mAb in a mouse tumor model, suggesting promising clinical prospects for this combination.